ANALISIS PENGARUH KUALITAS PRODUK DAN SERVICE QUALITY TERHADAP DAYA TARIK PRODUK SERTA DAMPAKNYA TERHADAP MINAT BELI - Satriadi, Ghani Annafi; Soesanto, Harry (Diponegoro Journal of Management, 2016)
This study aimed to analyze the influence of product quality and service quality to product appeal and that impact to purchase intention (study case on Garuda Indonesia aviation on society in Semarang). This study used two independent variables, there are product quality and service quality, purchase intention as a dependent variable and then product appeal as an intervening variable.A method of this research is using purposive sampling. The sample of this research are 100 respondents from civilian in Semarang that know about Garuda Indonesia aviation. Multiple regression analysis is used for this study.The results showed that product quality has positive effect to product appeal, service quality has positive effect to product appeal, and then product appeal has positive and significant effect to purchase intention